1993
DOI: 10.1071/pp9930099
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Oxidase Enzymes in the Sap and Skin of Mango Fruit

Abstract: Severe sapburn occurs in mango fruit of the cultivar Kensington when sap contacts the fruit, resulting in browning and then blackening of the skin. Both the sap and skin of mango fruit contained considerable polyphenol oxidase (PPO) activity. The sap enzyme was not activated by SDS, was inhibited by hexadecyltrimethylammonium bromide, and was active with both para- and ortho-diphenol substrates. The skin enzyme was activated by SDS, was inhibited by salicylhydroxamic acid and polyvinylpyrrolidone, and was acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 0 publications
6
69
1
2
Order By: Relevance
“…Though antisense transgenic sugarcane failed to suppress PPO activity and reduce the color intensity of juice and raw sugar, further attempts to lower PPO activity may still be warranted [62]. It was shown that sapburn (browning, blackening and necrosis of the skin) in mango fruits was induced by the sap and catalyzed by PPO in the skin [63]. This problem might be alleviated by producing transgenic mango with reduced PPO activity in this tissue.…”
Section: Application Of Transgenic Plants With Modified Ppo Activitymentioning
confidence: 99%
“…Though antisense transgenic sugarcane failed to suppress PPO activity and reduce the color intensity of juice and raw sugar, further attempts to lower PPO activity may still be warranted [62]. It was shown that sapburn (browning, blackening and necrosis of the skin) in mango fruits was induced by the sap and catalyzed by PPO in the skin [63]. This problem might be alleviated by producing transgenic mango with reduced PPO activity in this tissue.…”
Section: Application Of Transgenic Plants With Modified Ppo Activitymentioning
confidence: 99%
“…Wakayama (1994) also observed about 1.4 min to 2.4 min were required for 90% inhibition of the PPO from the core of six Japanese apple varieties. However, PPO from some other fruits such as banana (Chang et al, 2000), lichi (Ming et al, 1997) and mango sap (Robinson et al, 1993) offered higher resistance to thermal inactivation.…”
Section: Thermal Inactivationmentioning
confidence: 99%
“…PPO catalyses the conversion of monophenols into quinones, which has different spectral characteristics depending on the monophonols and pH (Robard et al 1999). In KP mango fruit, PPO activity was higher in the skin than in flesh and in ripe than green fruit (Robinson et al 1993). The role of PPO activity presumably becomes relatively more important in cell protection when mango fruit were ripe.…”
Section: Polyphenol Oxidasementioning
confidence: 93%
“…The role of PPO activity presumably becomes relatively more important in cell protection when mango fruit were ripe. The activity of PPO varied from cultivar to cultivar, being high in KP and low in Irwin mango fruit (Robinson et al 1993). Mango cultivar with high PPO activity on the fruit skin may be highly sensitive to LD.…”
Section: Polyphenol Oxidasementioning
confidence: 99%
See 1 more Smart Citation